A mixing‐flow reactor for time‐resolved reaction measurements distributed in space. Issue 2 (16th February 2022) - Beauvais, Michelle L.; Sanchez Monserrate, Bryan A.; Feng, Tianshi; Chen, Renkun; Liu, Ping; Chupas, Peter J.; Chapman, Karena W.
Abstract : A mixing‐flow reactor enables fast time‐resolved X‐ray scattering studies of solution‐phase reactions under flow. Abstract : Probing short‐lived reaction species is challenging owing to the need for both high signal‐to‐noise ratio, which can require long measurement time, and fast time resolution. Here, a novel in situ sample environment is presented that decouples time resolution from measurement time by distributing reaction time over space for the reaction under flow. In the mixing‐flow reactor, precursor solutions are mixed at a specific position along the flow path, where the reaction is initiated. As the reaction mixture flows within a reaction capillary, the reaction time increases with distance from the mixing point. A measurement can be taken at a specific distance from the mixing point for as long as is needed to accumulate good statistics without compromising the time resolution of the measurement. Applications of the mixing‐flow reactor for pair distribution function measurements of the initial nuclei formed during the hydrolysis of Al 3+ at high pH are shown.